2006
DOI: 10.1159/000092402
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 3 Is Estrogen-Responsive in utero and Upregulated during Sexual Differentiation

Abstract: Background/Aims: Synthetic estrogens induce hypospadias, an anomaly of genital tubercle/urethral development. Activating transcription factor 3 (ATF3), which is estrogen-responsive in vitro, is upregulated in hypospadiac human tissue. We used a mouse model of steroid-dependent genital tubercle development to elucidate the ontogeny of ATF3 expression and the developmental response of ATF3 in vivo to estrogen exposure. Methods: We used quantitative RT-PCR to assess ontogenic expression of ATF3 and its response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…From these genes, the activating transcription factor 3 (ATF3), a member of the ATF/CREB family of transcription factors (17), has been the gene with the greatest up-regulation. This gene has also been shown to be generally up-regulated during sexual differentiation (18). This evidence indicates a potential role of ATF3 in hypospadias and lead us to investigate ATF3 gene sequence in patients with this inborn error of development.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…From these genes, the activating transcription factor 3 (ATF3), a member of the ATF/CREB family of transcription factors (17), has been the gene with the greatest up-regulation. This gene has also been shown to be generally up-regulated during sexual differentiation (18). This evidence indicates a potential role of ATF3 in hypospadias and lead us to investigate ATF3 gene sequence in patients with this inborn error of development.…”
Section: Introductionmentioning
confidence: 85%
“…This effect may be due to disturbances on estrogenic responses during development (15,16,18). Moreover, ATF3 expression has also been reported to be up-regulated by the androgen receptor's activation by both androgens and estrogens in cell lines (27); this aspect indicate that variants in ATF3 may underlie androgenestrogen imbalances and influence the responsiveness to endocrine disrupters.…”
Section: Discussionmentioning
confidence: 99%
“…ATF3 was also upregulated in the penile skin tissues of boys with hypospadias 11) . It is of note that ATF3 has been strongly indicated as contributing to the development of hypospadias due to its estrogenresponsive character, since external estrogen causes mouse hypospadias and significantly upregulates ATF3 expression [12][13][14] . Because phthalates have been shown to mimic estrogen and are capable of binding to estrogen receptor 15,16) , we hypothesized that DEHP might also activate ATF3 of mouse GT.…”
mentioning
confidence: 99%
“…Also in vitro and some animal studies confirmed this finding [12]. Liu et al reported that fetal exposure to estrogen increased the level of ATF3 messenger RNA [13], whereas this group also indicated that fetal exposure to DEHP (di-2-ethylexyl phthalate) activated transcirption and transduciton of the ATF3 gene [14]. According to our clinical findings, we believed that there should be a dominant gene responsible for hypospadias formation in this family, but due to technical reasons, we could not have a chance to evaluate preputial samples and blood of patients for expression of ATF3 gene and genetic mutations.…”
Section: Case Reportmentioning
confidence: 59%